Research on the relationship between Wenling traditional dwellings-slabstone cottages and Changyudongtian quarries, China. Issue 5 (4th July 2019) - Fang, Jianping; Sun, Yali; Yang, Zhifa; Hu, Yunshi; Luo, Qiaohui
ABSTRACT: In this article, a type of traditional dwelling referred to as Wenling slabstone cottages, which are found in Aoli Village, Wenling City, Zhejiang Province, China is discussed. Stones are used as the main building materials of these dwellings, while they have seven characteristics that distinguish them from other traditional stone cottages. It was also determined in this article that the location of the Wenling slabstone cottages with distinct characteristics in Aoli Village was adjacent to the large ancient underground quarries of Changyudongtian. Moreover, it was confirmed that the latter provided important high-quality stone materials at low prices for the construction of the Wenling slabstone cottages. It was also pointed out in this article that with the rapid development of modern construction, the unreported Wenling slabstone cottages are gradually disappearing. Therefore, it is very important to carry out the exploration, research, and protection of these cottages in a timely manner.